Identifying Predisposing Causes and Consequences of Child Headed House Hold in the Case of Wolaita Sodo Town (Global Journal of Human-Social Science, 2017)
The main objective of the study is to explore predisposing factors, attitude and consequences of child headed house hold from both community member and the children perspective. To do so, a quantitative design was employed. Th e study was conducted in purposely selected five places in Wolaita sodo town. The required data were gathered from hundred respondents: fifty child headed house hold children and fifty community members. The main findings of the study show that Poverty, parental death, family conflict and large family size were predisposing factors for being child headed; the child headed house hold children have negative attitude or lower self-esteem towards themselves and Hopelessness, poorness, homelessness, migrates were found to be the consequences of being child headed house hold.